La red dorsal y los ‘costos jurídicos’ de mantener un proyecto que ya no es viable - Quiroga, María del Rosario (2021)
It is not difficult to identify the monetary costs derived from the execution of a major infrastructure project. That is why, when these projects fail to produce the expected results, they are labeled as ‘white elephants’: due to their high costs and low benefits. However, cost analysis tends to ignore the serious impact that a project can have on the legal system, especially when it involves a legal framework that is not fully coherent with other law principles and may enable authorities to perform arbitrary actions. The authors propose this to be the case of Peru’s National Dorsal Fiber Optic Network. More than five years after its implementation, the project cannot meet the market’s needs and has led to the issuance of contradictory and arbitrary decisions. This situation has affected some constitutional principles, such as legal predictability, a cost that must be considered when implementing future projects.